Machine Learning-Based Fake Profile Detection on Social Networking Websites - V. Mahesh; K. Tharun; P. Rushikesh; D. Saidulu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
These days social media has become an integral part of our lives, the challenge of detecting the fake accounts on platforms like Instagram, twitter, facebook etc. , . has gained significant importance. Each of these social media platforms offers benefits and drawbacks, as well as security risks for our information. This project titled "Instagram Fake Account Detection using Machine Learning", employs Python as its primary tool to tackle this problem. It leverages two powerful machine learning algorithms, the Random Forest Classifier and the Decision Tree Classifier, to accomplish this task.